(3JMUjd GdUMI HGdCSHGH GdSJIs - (3CHj GdaVd MHjT Hf EHQGgje Hf eMeO GdJadjSj,J (B600 (3g` s
(3ChdgG (B:s
(3bGd GdMHjTj GdJadjSj(B: (3CdaJ cJGHkG ef CbGhjd GdegQI ef GdSda hGdNda eTJedkG eYQaI bhGfjf JYOjd ddCSHGH GdSJI GdVQhQjI hgh eTJed Ydj CQHYI QSGFd s
(3BNQgG (B:s
(3jYbod YSd EPG de JfRY QZhJg CSgd hEf ofRYJ QHeG Ybd jYbd ZHjQkG jMHS cd SjdGf YSd GdbUH ojdjf GdHWf s
(3GdfSNI HgG MhGTs
(3HgG TQhMs
(3hHChdgG hBNQgG HYV cdeGJ HGdaGQSjIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs